2020
DOI: 10.1177/1362168820911189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating lists of high-frequency words: Teachers’ and learners’ perspectives

Abstract: With a number of word lists available for teachers to choose from, teachers and students need to know which list provides the best return for learning? Four well-established lists were compared and it was found that BNC/COCA2000 (British National Corpus / Corpus of Contemporary American English 2000) and the New General Service List (New-GSL) provided the greatest lexical coverage in spoken and written corpora. The present study further compared these two lists using teacher perceptions of word usefulness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 66 publications
1
50
0
Order By: Relevance
“…Finally, all but Nation’s lists seem to underestimate the knowledge of derived forms ( sexy, darkness ). A reassuring observation is that the two new General Service Lists include more of the words than the original list (see also Dang et al., 2020).…”
Section: Resultsmentioning
confidence: 95%
“…Finally, all but Nation’s lists seem to underestimate the knowledge of derived forms ( sexy, darkness ). A reassuring observation is that the two new General Service Lists include more of the words than the original list (see also Dang et al., 2020).…”
Section: Resultsmentioning
confidence: 95%
“…As a result, a number of high-frequency word lists have been created with the aim to represent highfrequency vocabulary: West's (1953) General Service List, Nation's (2006) list of the most frequent 2,000 words in the British National Corpus (BNC2000), Brezina and Gablasova's (2015) New General Service List, and Nation's (2012) most frequent 2,000 words in the British Nation corpus and the Corpus of Contemporary American English (BNC/ COCA2000). Given the number of available high-frequency word lists, subsequent studies (Dang & Webb, 2016a;Dang, Webb, & Coxhead, 2020) have been conducted using information from corpora, teachers, and learners to determine which list is the most relevant to EFL learners. In terms of the information from corpora, they compared the percentage of words covered by items from the four-word lists in 9 spoken corpora and 9 written corpora which represent various kinds of spoken and written discourse and varieties of English.…”
Section: Which Words Should Efl Learners Know?mentioning
confidence: 99%
“…Moreover, West's (1953) General Service List was used to represent high-frequency words in the Vocabulary Levels Test. The General Service List is dated and does not represent current vocabulary as well as Nation's (2012) BNC/COCA2000 (Dang & Webb, 2016a;Dang, Webb, & Coxhead, 2020).…”
Section: Efl Learners' Knowledge Of Highfrequency Wordsmentioning
confidence: 99%
“…The finding of recent research in Indonesia has shown that graded readers are beneficial to increasing Indonesian students' vocabulary (Hadiyanto, 2019). Besides that, the research of Dang, Webb, and Coxhead (2020) have suggested that it will be useful to learn words from the British National Corpus or Corpus of Contemporary American English 2.000 than other high-frequency word lists for the second language (L2) learners. Except for the one student who has mastered all the words from the 1 st until the 5 th 1.000 wordlevels, the rest of the participants are not yet ready to learn English from TED talks.…”
Section: Resultsmentioning
confidence: 99%